Association of high-sensitivity C-reactive protein and anemia with acute kidney injury in neonates - Peiyao Zhang; Peiyao Zhang; Yuanyuan Tong; Deshan Yuan; Yixuan Li; Yixuan Li; Yu Jin; Yu Jin; Liting Bai; Liting Bai; Peng Gao; Peng Gao; et al. (Frontiers Media S.A., 2022)
BackgroundThe association of high-sensitivity C-reactive protein (hsCRP) and anemia with postoperative acute kidney injury (AKI) in neonates with congenital heart disease (CHD) is still unclear. The purpose of this study was to examine whether anemia-associated AKI is modulated by hsCRP in neonates.MethodsThis study included 253 consecutive neonatal patients who underwent CHD surgery in a national tertiary hospital. We investigated the association between postoperative AKI with baseline hsCRP, anemia, and their interaction by multivariable logistic regression analyses.ResultsThe incidence of AKI was 24.1% in the entire cohort. After being adjusted for covariates, hsCRP level was negatively correlated with AKI (P < 0.01 for 1 mg/L threshold), whereas anemia emerged as an independent risk factor of AKI (P = 0.02). In addition, there was a significant interaction between anemia and hsCRP level (P = 0.01). In neonates with hsCRP < 1 mg/L, anemia was positively associated with AKI (P = 0.03). However, no significant association was found between anemia and AKI in the context of hsCRP ≥ 1 mg/L. Combination of anemia and hsCRP < 1 mg/L was independently correlated with the risk of AKI (P < 0.01), while concomitant anemia and hsCRP ≥ 1 mg/L or hsCRP < 1 mg/L combined with non-anemia was not.ConclusionsIn neonates with CHD, the risk of anemia-associated AKI may be modulated by hsCRP level. Attention should be paid to neonates with preoperative anemia and baseline hsCRP < 1 mg/L to reduce the risk of postoperative AKI.